2013
DOI: 10.1186/2049-1891-4-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel bacterial phytase expressed in Aspergillus Oryzae on digestibility of calcium and phosphorus in diets fed to weanling or growing pigs

Abstract: In 2 experiments, 48 weanling (initial BW: 13.5 ± 2.4 kg, Exp. 1) and 24 growing pigs (initial BW: 36.2 ± 4.0 kg, Exp. 2) were used to determine effects of a novel bacterial 6-phytase expressed in Aspergillus oryzae on the apparent total tract digestibility (ATTD) of phosphorus and calcium in corn-soybean meal diets fed to weanling and growing pigs. In Exp. 1 and 2, pigs were randomly allotted to 6 dietary treatments using a randomized complete block design and a balanced 2 period changeover design, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 41 publications
(70 reference statements)
11
33
0
Order By: Relevance
“…The reason for this response is most likely that as more bonds between P and phytate are hydrolyzed, less P can be released by additional phytase and at some point, no more P will be released regardless of the quantity of phytase in the diet. A similar response was previously reported for addition of phytase to diets based on corn or corn germ (Almeida and Stein, 2012) and also for diets based on corn and SBM (Almeida et al, 2013). The regression equations obtained in this experiment for SBM, CM-CV, and CM-HP most likely are also representative for other sources of these ingredients, but validation of the equations with different sources of SBM, CM-CV, and CM-HP is needed before wider usage is recommended.…”
Section: Regression Equationssupporting
confidence: 82%
“…The reason for this response is most likely that as more bonds between P and phytate are hydrolyzed, less P can be released by additional phytase and at some point, no more P will be released regardless of the quantity of phytase in the diet. A similar response was previously reported for addition of phytase to diets based on corn or corn germ (Almeida and Stein, 2012) and also for diets based on corn and SBM (Almeida et al, 2013). The regression equations obtained in this experiment for SBM, CM-CV, and CM-HP most likely are also representative for other sources of these ingredients, but validation of the equations with different sources of SBM, CM-CV, and CM-HP is needed before wider usage is recommended.…”
Section: Regression Equationssupporting
confidence: 82%
“…By contrast, the improvement in Ca availability found in this study is in accordance with the results found in many studies (BRAÑA et al, 2006;GUGGENBUHL et al, 2007;KIES et al, 2006;KIM et al, 2005KIM et al, , 2008POULSEN et al, 2010a;KAY, 2007;ALMEIDA et al, 2013;MADRID et al, 2013;FÁVERO et al, 2014;RUTHERFURD et al, 2014;KAHINDI et al, 2015), which show that phytase can effectively improve not only P availability but also Ca availability.…”
Section: Resultssupporting
confidence: 93%
“…In addition, part of the Ca complexed by the phytate molecule was liberated and available for the animals. These results confirms the efficacy of phytase in improving P and Ca availabilities and are in accordance with the findings of several researchers (KIM et al, 2005;BRAÑA et al, 2006;KIES et al, 2006;NYACHOTI et al, 2006;GUGGENBUHL et al, 2007;HTOO et al, 2007;POULSEN et al, 2007;MOEHN et al, 2007;KAY, 2007;KIM et al, 2008;POMAR et al, 2008;HILL et al, 2009;POULSEN et al, 2010aPOULSEN et al, , 2010bATAKORA et al, 2011;ALMEIDA et al, 2013;MADRID et al, 2013;FÁVERO et al, 2014;RUTHERFURD et al, 2014;KAHINDI et al, 2015) who verified improvements of P availability from 4.1% to greater than 100% with phytase addition in pig diets. This great range in P availability improvement is a consequence of differences in the design of the mentioned studies, such as the use of different feed ingredients, different phytase levels or activities, use of other enzymes in combination with phytase and diets with different nutrient levels.…”
Section: Resultssupporting
confidence: 92%
“…Several authors have reported an increment of Ca ATTD when the phytase enzyme has been added to the diet (Braña et al, 2006;Almeida et al, 2013) because Ca is chelated by phytic acid, regardless of its original form (Woyengo & Nyachoti, 2013). When phytase hydrolyses phytic acid, it releases the chelated Ca, making it available for the pigs to use.…”
Section: Discussionmentioning
confidence: 99%